Families and Brain Death - Kompanje, Erwin J. O. (Seminars in Neurology, 2015)
It is necessary to support the family of a patient with a progressively worsening severe acute brain injury, and to do this with the utmost understanding of their ultimate hopelessness. Any conversation starts with an explanation of the catastrophic nature of the illness, but also with establishing the point of no return. When brainstem reflexes are lost and the patient has become apneic, family members should be appropriately informed. In contrast to circulatory death, the relatives of such a patient do not see a deceased person in the traditional sense, and even the neurologic progression may not have been obvious to family members. The conversation about brain death with the close relatives is therefore different, and is more detailed than a conversation about cardiopulmonary death. In this review, a six-phase approach of communication with the relatives is proposed. Insightful snippets of personal conversations with family members are included. Communicating with family members also necessarily involves a discussion on the potential suitability for organ donation. Some suggestions on how to approach reluctant family members to accept death of their loved one are included.
Keywords: brain death; family-centered care; communication; organ transplantation